Clonal evolution and clinical implications of genetic abnormalities in blastic transformation of chronic myeloid leukaemia - Yotaro Ochi (Nature Portfolio, 2021)
In chronic myeloid leukaemia (CML), the drivers of blast crisis and resistance to tyrosine kinase inhibitors are not fully characterised. Here, the authors analyse a cohort of CML samples with genomic technologies and find that at least one driver alteration is associated with progression and worse prognosis.